Millennial Parents’ Health and Nutrition Literacy: A Survey in Tangerang Regency - Fitria Budi Utami; R. Sri Martini Meilanie; Fasli Jalal (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2025)
This study aims to analyze the level of health and nutrition literacy among millennial parents in Tangerang Regency, a strategic demographic due to their high exposure to digital technology and frequent involvement in child-health decision-making. A descriptive quantitative approach was employed involving 160 respondents selected through purposive sampling from several districts. Data were collected using an online questionnaire consisting of 26 items adapted from established health literacy frameworks and nutrition literacy instruments, covering four key dimensions: nutrition knowledge, information-seeking behavior, child-feeding practices, and utilization of health services. Descriptive statistics were used to map literacy patterns and parental practices. Findings indicate that 86.2 percent of respondents understand the concept of balanced nutrition, yet only 20.7 percent consistently read food labels. Additionally, 53.4 percent seldom apply nutrition information in daily routines, suggesting that nearly half of the participants have not yet translated their literacy into effective practice. Most respondents rely on social media platforms for information, while the use of official sources and health professionals remains limited. Based on health literacy frameworks, the majority fall within the functional literacy level, with relatively limited critical literacy skills. These results highlight the need for community-based and digital education interventions to strengthen practical and evaluative competencies in making informed family nutrition decisions